POTENSI PEMANFAATAN ITIK AFKIR SEBAGAI SUMBER DAGING ALTERNATIF DI WILAYAH PURWOKERTO: KAJIAN KETERSEDIAAN, KUALITAS, DAN STRATEGI PENINGKATAN NILAI TAMBAH - Supranoto Supranoto (Media Peternakan, 2022)
Culled ducks, namely laying ducks whose productivity has declined around 2–2.5 years of age, are continuously available in the Purwokerto region and its surroundings, which is one of the duck farming centers in Central Java. So far, culled ducks have not been utilized optimally because their meat is tough, has a fishy off-flavor, and contains relatively high fat, resulting in low economic value. This review aims to examine the availability, quality characteristics, challenges, and strategies to increase the added value of culled duck meat in the Purwokerto region, based on a literature review of the 2010–2020 period. The review shows that the weaknesses of culled duck meat can be overcome through marination with plant proteolytic enzymes such as bromelain (pineapple), papain (papaya), and zingibain (ginger), which improve tenderness, and through the use of spices such as turmeric and ginger to reduce off-flavor. Product diversification, such as nuggets, meatballs, shredded meat (abon), and jerky (dendeng), has been shown to improve tenderness while increasing economic value. With the availability of inexpensive raw materials, the support of a duck-based culinary market in Purwokerto, and the application of simple processing technologies, culled ducks have the potential to become an alternative meat source that is nutritious, economical, and supportive of food security and the local livestock economy.